Prinsip Dasar Aspek Distribusi dalam Ekonomi Islam: Rekonstruksi Filosofis Berbasis Maqashid al-Shari'ah dan Formulasi Kebijakan Kontemporer - Muslim, Nurul; Iska, Syukri (Universitas Dharma Andalas, 2026)
This article aims to reconstruct the fundamental principles of distribution in Islamic economics through the maqashid al-shari’ah approach and examine their relevance in a contemporary policy context, particularly in Indonesia. Employing a qualitative research method with a critical literature review design, the article analyzes normative sources (the Qur’an and Sunnah), classical to contemporary Islamic economic thought, and global inequality data. The findings identify three philosophical pillars that form a coherent Islamic distribution paradigm: first, the Trusteeship Theory of Ownership, which rejects absolute individual rights and establishes intrinsic social responsibility; second, Multi-Dimensional Distributive Justice, which is preventive, corrective, and participatory; third, Institutionalized Social Solidarity, which positions the state as an active guarantor. These three pillars are organically integrated with the objectives of Shariah (maqashid), particularly the preservation of wealth (hifz al-mal) and life (hifz al-nafs). The article further formulates a strategic implementation framework for Indonesia, including proposals for integrating zakat as a tax credit, strengthening Islamic inclusive finance, and optimizing productive waqf. It is concluded that the Islamic distribution paradigm offers a holistic and humanistic alternative to the failures of the dominant economic system, with significant potential to contribute to reducing structural inequality if implemented through creative socio-economic ijtihad and coordinated policies Abstrak Artikel ini bertujuan untuk merekonstruksi prinsip-prinsip dasar distribusi dalam ekonomi Islam melalui pendekatan maqashid al-shari’ah dan menguji relevansinya dalam konteks kebijakan kontemporer, khususnya di Indonesia. Menggunakan metode penelitian kualitatif dengan desain studi literatur kritis, artikel ini menganalisis sumber normatif (Al-Qur’an dan Sunnah), pemikiran ekonomi Islam klasik hingga kontemporer, serta data empiris ketimpangan global. Hasil penelitian mengidentifikasi tiga pilar filosofis yang membentuk paradigma distribusi Islam yang koheren: pertama, Teori Kepemilikan Amanah yang menolak hak mutlak individu dan menetapkan tanggung jawab sosial intrinsik; kedua, Keadilan Distributif Multi-Dimensi yang bersifat preventif, korektif, dan partisipatif; ketiga, Solidaritas Sosial Terlembagakan yang menempatkan negara sebagai penjamin aktif. Ketiga pilar ini terintegrasi secara organik dengan tujuan syariah (maqashid), khususnya penjagaan harta (hifz al-mal) dan jiwa (hifz al-nafs). Artikel ini selanjutnya merumuskan kerangka implementasi strategis di Indonesia, termasuk proposal integrasi zakat sebagai kredit pajak, penguatan keuangan inklusif syariah, dan optimalisasi wakaf produktif. Disimpulkan bahwa paradigma distribusi Islam menawarkan alternatif yang holistik dan humanis terhadap kegagalan sistem ekonomi dominan, dengan potensi signifikan untuk berkontribusi pada pengurangan ketimpangan struktural jika diimplementasikan melalui ijtihad sosio-ekonomi yang kreatif dan kebijakan yang terkoordinasi.